Germination response to water availability in populations of Festuca pallescens along a Patagonian rainfall gradient based on hydrotime model parameters - López, Aldana Soledad (2021)
Fil: López, Aldana Soledad. Instituto Nacional de Tecnología Agropecuaria (INTA). Centro Regional Patagonia Norte. Estación Experimental Agropecuaria Bariloche (EEA Bariloche). Instituto de Investigaciones Forestales y Agropecuarias Bariloche (IFAB). San Carlos de Bariloche, Río Negro, Argentina.